2014
DOI: 10.1109/tap.2014.2330584
|View full text |Cite
|
Sign up to set email alerts
|

Convex Optimization of Wireless Power Transfer Systems With Multiple Transmitters

Abstract: Wireless power transfer systems with multiple transmitters promise advantages of higher transfer efficiencies and focusing effects over single-transmitter systems. From the standard formulation, straightforward maximization of the power transfer efficiency is not trivial. By reformulating the problem, a convex optimization problem emerges, which can be solved efficiently. Further, using Lagrangian duality theory, analytical results are found for the achievable maximum power transfer efficiency and all paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 23 publications
1
43
0
Order By: Relevance
“…As shown in [2], the process of optimizing these parameters leads to closed-form expressions, whereby the optimal receiver load resistance R L , the receiver reactance x r , as well as the transmitter currents i t,n can be obtained from the impedance matrix Z of the WPT system, directly.…”
Section: System Setups and Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in [2], the process of optimizing these parameters leads to closed-form expressions, whereby the optimal receiver load resistance R L , the receiver reactance x r , as well as the transmitter currents i t,n can be obtained from the impedance matrix Z of the WPT system, directly.…”
Section: System Setups and Optimizationmentioning
confidence: 99%
“…As a result, wireless power transfer (WPT) systems have been widely studied both theoretically and experimentally. It has been demonstrated that multiple-input single-output (MISO) systems feature advantages compared to single-input single-output (SISO) systems, most importantly higher power transfer efficiency [1], [2]. This paper explores further advantages associated with such MISO WPT systems, particularly in terms of operating magnetic field strengths and exposure levels.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to one transmitter, multiple transmitters have more degree of freedom of the input current distribution and, therefore, provide the possibilities of efficiency enhancement as well as energy focusing toward target receiver. Maximum efficiency of multiple-transmitter system has been analyzed using linear programing or convex optimization [6,7,8]. However, these analyses give little physical insights into the system behavior, e.g., the relation between efficiency of the whole system and those of individual transmitter-receiver links.…”
Section: Introductionmentioning
confidence: 99%
“…Although substantial studies have been conducted on the performance limits of near‐field WPT, those of far‐field and low‐power rectennas are still critically lacking. For example, earlier studies have attempted to establish the theoretical limits of near‐field conversion efficiency by solving the associated convex programming problems . In addition, such maximum achievable efficiency of near‐field WPT has also been analyzed by using two‐port parameters and deriving a closed‐form analytic solution for the optimal load or performing numerical search for the optimal load under the transmitter‐diversity scheme .…”
Section: Introductionmentioning
confidence: 99%